1997
DOI: 10.1093/ajcn/66.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipemia in relation to sterol and fat excretion in ileostomy subjects given oat-bran and wheat test meals

Abstract: To investigate the mechanisms behind the serum cholesterol-lowering effect of oat fiber, we simultaneously measured postprandial lipid responses, serum lathosterol concentrations, and small bowel excretion of fat and sterols in ileostomy subjects given test meals high or low in oat fiber. Six ileostomy subjects (three women and three men) were served an oat-bran test meal (OB; 16.3 g fiber) and a wheat test meal (6.3 g fiber) in random order. After the postprandial 7-h period, a controlled, low-fat, cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 53 publications
5
49
1
2
Order By: Relevance
“…Addition of some dietary fibre sources into mixed test meals (Cara et al, 1992;Lia et al, 1997) at the level of 4-10 g/meal can moderately reduce postprandial triglyceridaemia or chylomicron lipids as generated by a mixed meal ( Table 2). Sources of soluble viscous fibres (i.e., oat bran) or with hypotriglycerdemic properties (i.e., wheat germ) were shown to display such an effect in line with the interference they generate on fat lipolysis within the gut.…”
Section: Dietary Fibresmentioning
confidence: 99%
“…Addition of some dietary fibre sources into mixed test meals (Cara et al, 1992;Lia et al, 1997) at the level of 4-10 g/meal can moderately reduce postprandial triglyceridaemia or chylomicron lipids as generated by a mixed meal ( Table 2). Sources of soluble viscous fibres (i.e., oat bran) or with hypotriglycerdemic properties (i.e., wheat germ) were shown to display such an effect in line with the interference they generate on fat lipolysis within the gut.…”
Section: Dietary Fibresmentioning
confidence: 99%
“…The total fat excretion observed was indeed similar to that observed by Lia et al who found that ileostomy patients consuming oat bran or wheat bran excreted 465 mg or 194 mg of fat=day, respectively. 31 These values correspond to 99.1 and 99.7% fat absorption for oat bran and wheat bran consumption, respectively. Earlier studies of the absorbability of fats in rats showed that coconut oil is 99.7% absorbed compared to 98% for lard.…”
Section: Discussionmentioning
confidence: 94%
“…As β−glucanas de cereais diminuem a taxa de colesterol plasmático, principalmente em indivíduos hipercolesterolêmicos [4,17,18,20] e atenuam a resposta glicêmica e insulínica pós-prandial [5,8,15], o que possibilita sua utilização no controle ou retardo do aparecimento de doenças crônicas, como doenças coronárias e diabetes melito [23].…”
Section: -Introduçãounclassified